SEPs, SSOs and FRAND : Asian and global perspectives on fostering innovation in interconnectivity - Liu, Kongzhong, 1961-; Hilty, Reto M., 1958- (New York : Routledge, 2019)
"This book is a very useful reference guide on how de jure and de facto standards are being developed and how these standards compete against each other. The book also looks at how FRAND commitments are being determined across countries, how these disputes have played out, especially in Asia, and how they can be better dealt with in future globally. The book gives a broad overview of the business model of dominant SEP patentees and analyzes some standards for FRAND licensing of SEPs which are converging in major Asian jurisdictions. It highlights the need for ex ante regulation in the FRAND licensing of SEPs and suggests how we can reconcile conflicts which may arise from different legal standards. This book provides detailed and comprehensive analysis of recent SEP cases with an emphasis on Asia and will interest anyone who wishes to have more insight into the legal, policy, industrial and economic implications of such issues"--
Introduction : As a Matter of Standard for Asia and Beyond? / Kung-Chung Liu -- De facto Standards / Jiyu Zhang -- De Jure Standard Setting in the Telecom Industry : Its Evolution and the Developing Country Case for Reform / Prashant Reddy Thikkavarapu -- Standard Setting Organizations, Standard-Essential Patents and FRAND Terms : An Economic Observation / Felix Conde, Lanhua Li and Can Huang -- US Perspectives / William Hubbard -- Asian Perspectives / Jyh-An Lee and Sang Jo Jong -- UK Perspectives / Peter Damerell and Tess Waldron -- Unprepared, Unable and Unwilling to Deal with FRAND Licensing of SEPs in Taiwan / Kung-Chung Liu -- Japan / Masabumi Suzuki -- Korea / Jinyul Ju -- IPR Protection and Antitrust Regulation of SEPs in China / Liyang Hou and Mengchi Tian -- Standard Essential Patents and FRAND Licensing : A View from India / -- Biswajit Dhar and Reji K. Joseph -- The Paradox of Relief: Reconciling Remedies in Patent Law and Competition Law for FRAND Cases in India / Feroz Ali -- FRAND as a Legal Concept at the Intersection between Competition Law and Intellectual Property Law : The Road Ahead for Singapore? / Burton Ong -- European Experiences: EU and Germany / Matthias Leistner -- Stakeholders' Views on Policy Concerns and Regulatory Framework for Self-regulation by SSOs / Fair Standards Alliance and Shengtao Hu -- Propositions for Regulated Self-regulation of SSOs / Kung-Chung Liu and Haoran Zhang
OCLC-licensed vendor bibliographic record.
Keywords: Foreign licensing agreements; Patent licenses; Standardization -- Law and legislation; Patents (International law); LAW / Intellectual Property / Patent; LAW / Intellectual Property / General; LAW / Commercial / General